The Use of Recombinant Antithrombin III in Pediatric and Neonatal ECMO Patients. Issue 1 (January 2017) - Todd Tzanetos, Deanna R.; Myers, John; Wells, Terri; Stewart, Dan; Fanning, Jeffrey J.; Sullivan, Janice E.
Abstract : A retrospective review of 77 pediatric and neonatal extracorporeal membranous oxygenation (ECMO) patients who received recombinant antithrombin III (ATIII) for ATIII activity greater than 80% was conducted. Anticoagulation management was per institutional protocol. An ATIII activity greater than 80% was targeted. Diagnosis, reason for ECMO cannulation, blood product usage, heparin dosing, ATIII activity and doses, thrombotic and bleeding complications, hours on ECMO, and mortality were recorded. We calculated patient-level summary statistics and assessed differences between groups using χ 2 tests (categorical variables) and Wilcoxon rank sum tests (continuous variables). Hierarchical generalized linear models were developed to model bleeding and thrombotic complications. The majority (n = 75) received venoarterial ECMO and had cardiac diagnoses (n = 62). Antithrombin III activity was below 80% for an average of 5.2 hours per patient. Antithrombin III activity less than 80% was not associated with thrombotic complications (odds ratio [OR] = 1.02, 95% confidence interval [CI] = 0.97–1.06, p = 0.86). Antithrombin III activity greater than 80% was not associated with bleeding complications (OR = 1.06, 95% CI = 1.01–1.11, p = 0.44). Duration of ECMO was an independent predictor of thrombotic complications (OR = 1.08, 95% CI = 1.02–1.11, p = 0.02). There were no independent predictors of bleeding complications. Antithrombin III activity correlated with anti Xa activity ( r = 0.367, p < 0.001) but not with other measures of anticoagulation or with heparin dose ( r = 0.16, p = 0.165). ATIII activity was not associated with bleeding, thrombosis, or heparin dose. Antithrombin III activity was associated with anti Xa activity but not with traditional measures of anticoagulation. Antithrombin III replacement for an activity less than 80% did not increase bleeding.